PENGARUH KEPUASAN PELANGGAN, SWITCHING BARRIER DAN KEPERCAYAAN PELANGGAN TERHADAP COSTUMER RETENTION DI AZZWARS PERFUME KOTA PADANG - Lidya Martha; Dwi Putra Anugrah (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to analyze the effect of customer satisfaction, switching barriers and customer trust on customer retention at Azzwars Perfume, Padang City. This study uses quantitative methods. The population is Azzwars Perfume Padang City customers as many as 3534 respondents and a sample of 100 respondents, the sampling technique is Probability Sampling with Simple random Sampling technique where the sampling of population members is done randomly so that each member of the population has the same opportunity to be sampled. Data analysis using Multiple Linear Regression analysis using SPSS application. The results showed that the influence of customer satisfaction had a positive and significant effect on Customer Retention at Azzwars Perfume, Switching Barrier had a positive and significant effect on Customer Retention at Azzwars Perfume, and Customer Trust had a positive and significant effect on Customer Retention at Azzwars Perfume, Padang City